IMPLEMENTASI PROGRAM SEKOLAH HIJAU BERBASIS PERTANIAN DALAM MENINGKATKAN KESADARAN LINGKUNGAN SISWA - Rahmat, Rahmat (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2024)
This study aims to analyze the implementation of an agriculture-based Green School Program in enhancing students’ environmental awareness at SMKN 1 Trucuk Klaten. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the program is systematically integrated into the vocational curriculum and school culture and implemented through experiential agricultural practices as a living laboratory. The integration of farming activities into productive learning, organic waste management into compost, school greening initiatives, and environmentally friendly behavioral habits contributes to students’ ecological awareness in cognitive, affective, and behavioral dimensions. Although challenges remain in measurable evaluation and consistent participation, the agriculture-based Green School Program has generally demonstrated a positive impact on fostering contextual and sustainable environmental character among students.